2013
DOI: 10.2139/ssrn.2214874
|View full text |Cite
|
Sign up to set email alerts
|

Early Child Care and Child Development: For Whom it Works and Why

Abstract: SOEPpapers on Multidisciplinary Panel Data Research at DIW Berlin This series presents research findings based either directly on data from the German SocioEconomic Panel Study (SOEP) or using SOEP data as part of an internationally comparable data set (e.g. CNEF, ECHP, LIS, LWS, CHER/PACO). SOEP is a truly multidisciplinary household panel study covering a wide range of social and behavioral sciences:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
31
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 44 publications
4
31
0
1
Order By: Relevance
“…Our study falls into the category of papers that focus on settings in which public childcare crowds out mainly family care. Most of the existing studies analyzing the consequences of public childcare crowding out family care focus on short-run effects on children's outcomes (Datta Gupta and Simonsen 2010;Felfe and Lalive 2012). The only exception is Drange et al (2012) who analyze the consequences of a reform in Norway in 1997 that lowered the mandatory school starting age from 7 to 6 in terms of children's cognitive outcomes at the end of mandatory schooling.…”
Section: Introductionmentioning
confidence: 99%
“…Our study falls into the category of papers that focus on settings in which public childcare crowds out mainly family care. Most of the existing studies analyzing the consequences of public childcare crowding out family care focus on short-run effects on children's outcomes (Datta Gupta and Simonsen 2010;Felfe and Lalive 2012). The only exception is Drange et al (2012) who analyze the consequences of a reform in Norway in 1997 that lowered the mandatory school starting age from 7 to 6 in terms of children's cognitive outcomes at the end of mandatory schooling.…”
Section: Introductionmentioning
confidence: 99%
“…For example, evidence from a German study on the effect of kindergarten attendance on secondary schooling shows a compensatory effect only for migrant children (Spiess et al 2003). Another recent study from Germany (Felfe and Lalive 2013) found compensatory effects of highquality centre-based care on inequalities in a wide range of skills across children. Although children from more advantageous backgrounds are more likely to be enrolled in high-quality centre-based care, they profit the least; whereas children from less advantageous backgrounds are less likely to attend, but gain the most.…”
Section: Are the Effects Of Early Education And Care Lasting?mentioning
confidence: 99%
“…(Gormley Jr. et al, 2008), Kаskio (Cascio, 2009), Mаgnuson i sаr. (Magnuson et al, 2004), Pješčić (1977), Ficpаtrik (Fitzpatrick, 2008), Hаvns i Mogstаd (Havnes & Mogstad, 2011), Felfe i Lаliv (Felfe & Lalive, 2012) i Felfe i sar. su direktno vezаnа i zа pitаnjа kojа postаvljаmo u ovom rаdu.…”
Section: Veza Između Programa Predškolskog Obrаzovаnjа I Vaspitanja Imentioning
confidence: 99%
“…imа preko 100% više, nego među učenicimа koji nisu bili obuhvаćeni predškolskim vаspitаnjem". Felfe i Laliv (Felfe & Lalive, 2012) takođe zaključuju da "univerzalno (predškolsko, p.a.) vaspitanje može čak da doprinese smanjenju nejednakosti između dece koja dolaze iz različitih socio-ekonomskih sredina".…”
Section: Veza Između Programa Predškolskog Obrаzovаnjа I Vaspitanja Iunclassified